Quasi-Asymptotic Behavior at Infinity of Tempered Operators - Nemzer, Dennis (Sarajevo Journal of Mathematics, 2024)
A subspace of Mikusiński operators, which was introduced by K. Yosida, is used to investigate quasi-asymptotic behavior at infinity in one dimension.